Contrasting physiological responses to future ocean acidification among Arctic copepod populations. (21st September 2017) - Thor, Peter; Bailey, Allison; Dupont, Sam; Calosi, Piero; Søreide, Janne E.; De Wit, Pierre; Guscelli, Ella; Loubet‐Sartrou, Lea; Deichmann, Ida M.; Candee, Martin M.; Svensen, Camilla; King, Andrew L.; et al.
Abstract: Widespread ocean acidification (OA) is modifying the chemistry of the global ocean, and the Arctic is recognized as the region where the changes will progress at the fastest rate. Moreover, Arctic species show lower capacity for cellular homeostasis and acid‐base regulation rendering them particularly vulnerable to OA. In the present study, we found physiological differences in OA response across geographically separated populations of the keystone Arctic copepod Calanus glacialis . In copepodites stage CIV, measured reaction norms of ingestion rate and metabolic rate showed severe reductions in ingestion and increased metabolic expenses in two populations from Svalbard (Kongsfjord and Billefjord) whereas no effects were observed in a population from the Disko Bay, West Greenland. At pHT 7.87, which has been predicted for the Svalbard west coast by year 2100, these changes resulted in reductions in scope for growth of 19% in the Kongsfjord and a staggering 50% in the Billefjord. Interestingly, these effects were not observed in stage CV copepodites from any of the three locations. It seems that CVs may be more tolerant to OA perhaps due to a general physiological reorganization to meet low intracellular pH during hibernation. Needless to say, the observed changes in the CIV stage will have serious implications for the C. glacialis population health status and growth around Svalbard. However, OA tolerant populations such as the one in the Disko Bay could help to alleviate severe effects in C. glacialis as a species. Abstract : Ocean acidification is most severe in the Arctic. Decreased seawater pH induced severe reductions in ingestion (filled circles) and increased metabolic expenses (open circles) in copepodite stage CIV of the key stone copepod species Calanus glacialis in the Kongsfjord (a) and the Billefjord (c) whereas no effects were observed in a population from the Disko Bay, West Greenland (b). Although these changes were not observed in the later copepodite CV stage, they will have detrimental effects on adult body size and ultimately egg production. Future OA will therefore pose a challenge to C. glacialis populations around Svalbard whereas other populations, as in the Disko Bay, may be left unchanged.